Longitudinal Associations between Parenting and Inattention, Impulsivity, and Delay of Gratification in Preschool-aged Children: The Role of Temperamental Difficultness and Toddler Attention Focusing. Issue 5 (3rd July 2020) - Conway, Anne
ABSTRACT: Data from the National Institute of Child Health and Human Development Study of Early Child Care were used to test whether maternal sensitivity and stimulation at 15 and 54 months predicted child attention, impulsivity, and delay of gratification at 54 months, and whether toddler attention and temperamental difficultness moderated associations. Maternal sensitivity at 54 months was positively associated with children's delay of gratification and negatively associated with inattention and impulsivity at 54 months. Maternal stimulation at 15 months was negatively associated with inattention at 54 months for toddlers with higher levels of attention focusing and temperamental difficultness. The importance of attending to individual differences is discussed.